Hubungan Karakteristik Pasien dengan Kepatuhan Minum Obat pada Pasien Hipertensi Berdasarkan Skala MMAS-8 - Apriani, Aida; Sirait , Tri Susanti; Silitonga , Desni Rinanda; Zawita, Zawita (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2026)
Background: Hypertension is classified as a non-communicable disease with a relatively high prevalence and poses a significant risk of various complications if not properly managed or controlled. Medication adherence plays a crucial role in determining the success of antihypertensive therapy. Objective:This study aimed to analyze the level of medication adherence among hypertensive patients at Pidie Jaya General Hospital using the Morisky Medication Adherence Scale (MMAS-8) instrument. Methods:This research employed a descriptive-analytic design with a cross-sectional approach involving 98 hypertensive patients selected using the Slovin formula. Data were collected using the MMAS-8 questionnaire and analyzed using the Chi-square test with a significance level of p < 0.05. Results:The findings showed that medication adherence among respondents was categorized as adherent (26.5%), moderately adherent (58.2%), and non-adherent (15.3%). There were no significant associations between adherence and sex, age, education, occupation, duration of treatment, number of medications, or family support (p > 0.05). However, a significant relationship was found between medication adherence and the distance from the patient's residence to the healthcare facility (p = 0.001). Conclusion: Distance to treatment affects the level of compliance of hypertensive patients with medication. Therefore, strategies are needed to improve access to healthcare services, including optimizing clinical pharmacy services to monitor patient compliance.